The Effect of Service Quality and Marketing Mix on Airport Train Customer Loyalty at BNI City Station Mediated by Customer Value - Putra, Derry Herlasetyadi; Abidin, Zaenal; Agusinta, Lira; Gunawan, Aang; Fachrial, Peppy (Devotion : Journal of Research and Community Service, 2024)
This research aims to analyze the mediating role of customer value on the influence of service quality and marketing mix on Soekarno-Hatta International Airport train customer loyalty. This research was carried out from March to May 2021 at BNI City Station. The population in this study were passengers who had used the airport train at BNI City Station. The sample method uses random samples. The data analysis method in this research uses Structural Equation Model Partial Least Square (SEM-PLS) with the help of SmartPLS 3.2.9. The results in this study show that service quality has a positive effect on customer loyalty, service quality has a positive effect on customer value, marketing mix has a positive effect on customer loyalty, marketing mix has a positive effect on customer value, customer value has a positive effect on customer loyalty, service quality has a positive effect on customer loyalty with the mediation of customer value,  the marketing mix has a positive effect on customer loyalty with the mediation of customer value for the Soekarno-Hatta International International Airport train at BNI City Railway Station.